Penyuluhan Kesehatan Mengenai Cara Penanganan Febris (Demam) Dan Pemberian Kompres Hangat Untuk Mengurangi Demam Di RSI Muhammadiyah Singkil Kabupaten Tegal - Ahmad Zakiudin; Djoko Aji; Devi Munfaiqoh; Vicky Liza Nabila (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Fever is a body condition above normal (>37.5 0C). As a result of an increase in the temperature regulation center in the hypothalamus. Most fevers in children are the result of changes in the heat center (thermoregulation) in the hypothalamus. Diseases characterized by fever can attack the body's systems. Apart from that, fever plays a role in increasing the development of specific and non-specific immunity in helping recovery or defense against infection. The aim of this activity is to be able to understand fever and giving warm compresses to find out the efficacy of warm compresses in febrile patients. Health education about fever and warm compresses can increase public knowledge to make every effort to treat fever with warm compresses.